Me and Others Around: The Roles of Personal and Social Norms in Chinese Adolescent Bystanders’ Responses Toward Cyberbullying - Dang, Jianning (Journal of interpersonal violence, 2022)
Researchers have expanded the aggressor-victim dyad by showing that bystanders play pivotal roles in the process of cyberbullying. Bystanders? responses entail moral engagement and are guided by personal and social norms. Most research on normative influences on bystanders? responses to cyberbullying has focused on personal or social norms but has ignored how they jointly affect bystanders? responses. Inspiring by the modified Theory of Planned Behavior, a cross-sectional study of Chinese high-school students (N = 333) examined how cyberbullying-related personal and social norms affect adolescent bystanders? responses to cyberbullying. We collected information on personal norms, social norms, and bystanders? responses to cyberbullying. Boys reported stronger intentions than girls to reinforce the bully, but intentions to help the victim were equivalent among boys and girls. Regression analysis revealed that pro-cyberbullying personal and social norms combined could negatively predict intentions to help the victim. However, personal and social norms interacted to influence behavioral intentions to reinforce the bully. Specifically, when pro-cyberbullying social norms were at a high level, a higher level of pro-cyberbullying personal norms was correlated with higher intentions to reinforce the bully. Conversely, when pro-cyberbullying social norms were at a low level, the effect of personal norms disappeared. The findings contribute to understanding the process by which adolescents adapt themselves to norms and provide guidance for educational advice on intervening in cyberbullying.